DEVELOPMENT OF MEASUREMENTâS RELIABILITY AND ACCURACY FOR TIMING GATE SYSTEM - Barnaby Wirantono Goeij, Ethan
Indonesia has a big potential in terms of human resources, however Indonesia’s achievements related to sport activities are still lacking and in need of a massive improvements. This lack can be overcome by facilitating tools that can support athlete’s development. One of the tools that can support athlete’s development is an accurate and reliable time measurement tool. Lately in ITB, there has been developed a digital time measurement tool, called as timing gate, which utilize photoelectric sensor, with relatively affordable price, to comply with local needs. However, the timing gate still needs a further research to improve its measurement reliability and accuracy. This research is held with the aim to improve the reliability and accuracy of the timing gate. This research is focused on the measurement’s sensor hardware and measurement configuration. The steps of this research started from deciding the hardware used such as the sensor and the supporting components. The decisions are based upon the hardware reliability, affordability, and whether the hardware is suitable for sport related activities. Next step of the research was developing and implementing software for the sensor, so that the sensor is able to measure athlete’s torso time duration. Then the last step was developing a system of sensors with wireless communication so that all the sensors is connected to one data gathering center. Based upon the tests done, the prototype has proven to have a better reliability than the previous developed timing gate prototype from 16% to 90%, because of the current ability to better withstand ambient light. This protoype also has an algorithm to reject disturbance (noise). This prototype is able to be used in 40 meter sprint test. However, the measurement accuracy of this prototype still depends on the wireless communication signal strength. The stronger the signal, the better the accuracy will be.